2020
DOI: 10.1038/s41598-020-66639-w
|View full text |Cite
|
Sign up to set email alerts
|

Non-canonical chemical feedback self-limits nitric oxide-cyclic GMP signaling in health and disease

Abstract: Nitric oxide (NO)-cyclic GMP (cGMP) signaling is a vasoprotective pathway therapeutically targeted, for example, in pulmonary hypertension. Its dysregulation in disease is incompletely understood. Here we show in pulmonary artery endothelial cells that feedback inhibition by NO of the NO receptor, the cGMP forming soluble guanylate cyclase (sGC), may contribute to this. Both endogenous NO from endothelial NO synthase and exogenous NO from NO donor compounds decreased sGC protein and activity. This effect was n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…These agonists provided a means to assess the relative levels of the different sGC forms present in cells or tissues. They have been utilized in studies with human umbilical vein endothelial cells, primary human airway smooth muscle cells, a cell line that naturally expresses sGC (RFL6), transfected COS-7 or HEK cells, and tissues from a number of animal disease models ( 53 , 65 , 66 , 67 , 68 , 69 ). In all cases, results with the pharmacologic agonists indicated that heme-free or heme-oxidized forms of sGC were present.…”
Section: Sgc Maturation To a Heterodimermentioning
confidence: 99%
“…These agonists provided a means to assess the relative levels of the different sGC forms present in cells or tissues. They have been utilized in studies with human umbilical vein endothelial cells, primary human airway smooth muscle cells, a cell line that naturally expresses sGC (RFL6), transfected COS-7 or HEK cells, and tissues from a number of animal disease models ( 53 , 65 , 66 , 67 , 68 , 69 ). In all cases, results with the pharmacologic agonists indicated that heme-free or heme-oxidized forms of sGC were present.…”
Section: Sgc Maturation To a Heterodimermentioning
confidence: 99%
“…Indeed, under physiological conditions, treatment with an sGC activator only accounts for a small amount of sGC activity compared to NO 16 . However, under high NO conditions, Fe(II)sGC is known to be degraded, hence sGC signalling can be functionally recovered in a mechanism-based manner by apo-sGC activators that re-establish cGMP formation 45 .…”
Section: Discussionmentioning
confidence: 99%
“…It will be useful to explore if specific SNO modifications destabilize the sGC heterodimer or promote complex formation between the haem-containing sGCβ subunit and Hsp90. By resolving the molecular changes to sGCβ and the sGC heterodimer that take place during NOC12 inactivation in cells, our work helps to explain how NO can engage in non-canonical feedback to self-limit NO-driven cGMP signalling in health and disease (Dao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%